If A = {2, 3}, B

given: A = {2, 3}, B = {4, 5} and C = {5, 6}

To find: (A × B) (A × C)

Since, (B C) = {4, 5, 6}

A × (B C) = {(2, 4), (2, 5), (2, 6), (3, 4), (3, 5), (3, 6)}

(A × B) = {(2, 4), (2, 5), (3, 4), (3, 5)}

(A × C) = {(2, 5), (2, 6), (3, 5), (3, 6)}

(A × B) (A × C) = {(2, 4), (2, 5), (2, 6), (3, 4), (3, 5), (3, 6)}

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

State True Mathematics - Exemplar

If [x]2</supMathematics - Exemplar

State True Mathematics - Exemplar

Let A = {3, 4, 5,RS Aggarwal - Mathematics

Let R = {(a, b) :RS Aggarwal - Mathematics

Let A = (1, 2, 3}RS Aggarwal - Mathematics

Is the given relaMathematics - Exemplar

Let R = {(x, y): RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Let A = {2, 3} anRS Aggarwal - Mathematics